DAMPAK PEMBELAJARAN ONLINE TERHADAP KESEHATAN MENTAL PADA ERA PANDEMI COVID-19: DAMPAK PEMBELAJARAN ONLINE TERHADAP KESEHATAN MENTAL PADA ERA PANDEMI COVID-19 - Okki Muhammad Fajar Muthahhari; Rani Himayani; Rizki Hanriko (Medula, 2023)
COVID-19, which spread throughout the world, causing the disease to be declared a pandemic, has affected all aspects of people's lives without exception in the world of education, which was previously conducted face-to-face, now the learning method has changed to online learning. This causes many things to be done by using communication tools as a socializing chain with the surrounding environment. Online education is a new method of learning through networks that has been in place since early 2020, which is one of the steps to reduce the spread of COVID-19. Distance Education can have an impact on students' psychology. This causes many things to be done by using communication tools as a socializing chain with the surrounding environment. Mental health is becoming a problem in the midst of the COVID-19 pandemic, especially for elementary school students. Mental health is constantly changing, creating a variety of major problems that must be resolved. This article aims to determine the mental health of students while undergoing online learning during the COVID-19 pandemic era. The type of review used in this journal is in the form of a literature review of 40 articles found through the NCBI database, PubMed, Google Scholar, only 22 articles were selected from 2020 to 2022. The result of this article is to explain the latest updates regarding the impact of online learning in the era of the COVID-19 pandemic. 19 on mental health.